CONSTITUTIONAL LEGAL RESPONSIBILITY FOR CRIMES AGAINST STATE UNITY AND TERRITORIAL INTEGRITY OF RUSSIA - S. V. Ivanov (Правоприменение)
The subject. The article is devoted to the issues of constitutional legal responsibility for crimes against the state unity and territorial integrity of the Russian Federation.The purpose of the article is to reveal the actual problems of constitutional legal responsi-bility for crimes against the state unity and territorial integrity of the Russian Federation.The methodology of the study includes general scientific methods (analysis, synthesis, com-parative method, description) as well as particular academic methods (formal-legal method, interpretation of legal acts).Results, scope. The article contains the analysis of the position of the state unity and territorial integrity of the Russian Federation among the objects of constitutional legal and crim-inal legal support. The specific features of constitutional legal responsibility for crimes against the state unity and territorial integrity of Russia are determined. Actual problems of constitutional legal responsibility of the President of the Russian Federation, Russian cit-izens, refugees, electoral candidates for crimes against its state unity and territorial integ-rity are revealed.Conclusions. It is necessary to improve the current constitutional legislation in order to elim-inate the existing problems of constitutional legal responsibility for crimes against the state unity and territorial integrity of the Russian Federation. For this purpose it is necessary to add the grounds for impeachment of the President of the Russian Federation by the fact of commission of crime against its state unity and territorial integrity. It is also necessary to eliminate the legal inequality of citizens formed as a result of the introduction of constitu-tional and legal responsibility of naturalized citizens for committing crimes defined by law.